Mathematical representation ability on geometry material viewed from interest for learning in jigsaw cooperative learning performance assessment - Elmagustilla, Sheila Rosita; Masrukan, Masrukan (Department of Mathematics, Universitas Negeri Semarang, 2021)
This research aimed to test whether Jigsaw cooperative learning on geometry material with performance assessment achieve mastery learning, test whether the ability of the mathematical representation of students with Jigsaw cooperative learning on geometry material with the assessment of the performance is better than the ability of the representation of the students on the model of Discovery Learning, a description of the ability of the mathematical representation students on Jigsaw cooperative learning with the assessment of performance in terms of student interest. This study is mixed-methods research. The subjects were students of class VIII-A, one of Junior High School in Kaliwungu. The data collection method with tests, questionnaires and interviews. The results showed that: mathematical representation abilities of students who receive Jigsaw cooperative learning on geometry material with performance assessment fulfil the completeness of learning, mathematical representation abilities of students on geometry material in Jigsaw cooperative learning with performance assessments better than mathematical representation abilities of students on Discovery Learning, and descriptions of students' mathematical representation abilities in the Jigsaw cooperative learning with performance assessments in terms of students interest learning that students with high learning interest are able to fulfil indicators of mathematical representation ability is very well, students with learning interest are able to fulfil indicators of mathematical representation ability well and students with low learning interest are less able to fulfil the indicators of mathematical representation ability.